Homocysteine and vitamin status in healthy Thai smokers - Kanjana Suriyaprom (2018)
Purpose. Cigarette smoking is considered to increase morbidity and the mortality risk of cardiovascular diseases. B vitamins regulate the metabolism of homocysteine via remethylation and trans-sulfuration pathways. The purpose of this study was to investigate homocysteine concentrations, vitamin status, anthropometric and haematological measurements of healthy smokers compared with healthy non-smoking subjects. Design. This cross-sectional study was carried out among smokers and non-smokers from suburban and urban residential areas in Bangkok, Thailand. Materials and methods. 174 smokers and 97 non-smokers (aged 19-62), who participated voluntarily in the study, were investigated. Total homocysteine, folate, vitamin B2, B6, B12, and C concentrations were measured. Results. Total homocysteine concentrations in plasma were significantly higher in smokers than non-smokers. Vitamin B2, folate, B12and C concentrations were significantly lower among smokers than non-smokers but vitamin B6was not significantly different between these groups. Total homocysteine concentration had a significantly positive correlation with waist/hip ratio and smoking characteristics such as the number of cigarettes per day and pack-years but a significantly negative association with folate and vitamin B12. There were significant positive associations among the number of cigarettes smoked per day, white blood cell (WBC) count and waist/hip ratio. Furthermore, the prevalence of hyperhomocysteinemia in smokers (62%) was more common than in non-smokers (33%). Conclusion. These findings suggest that increased plasma total homocysteine concentrations in healthy Thai smokers may be explained by a low status of the B vitamins that are involved in homocysteine metabolism such as vitamin B2, folate, and B12. The elevation of the number of cigarettes smoked per day and pack-years, WBC count, and high percentage of hyperhomocysteinemia among smokers may contribute to increased risk of atherosclerosis or the development of cardiovascular disease. © 2005 Taylor & Francis.